The Role of PGMI Teachers in Internalized Islamic Values in Students at SDN 35 Bengkulu City - Ullik Nurhalimah; Putri Mustriana Mukhasonah; Ahmad Suradi; Dalima Septiria (MODELING: Jurnal Program Studi PGMI, 2024)
The current rise in moral and ethical crises has affected and damaged Indonesia's young generation. This is due to numerous factors, including inappropriate social interactions, the circulation of inappropriate videos and images among teenagers, and a lack of religious knowledge and guidance. To address this moral and ethical crisis among young people, the Indonesian government has taken aggressive action by implementing character education in schools. Addressing this problem is, of course, the responsibility of PGMI teachers. This study aims to determine the role and efforts of PGMI teachers in internalizing Islamic character values ??among students at SDN 35, Bengkulu City, and the forms of Islamic character values ??that students should possess. This research method uses a descriptive qualitative approach. Data collection techniques are drawn from primary sources in the form of interviews and secondary sources in the form of literature studies such as books and journals related to this discussion. The results of this study indicate that the role of PGMI teachers in internalizing Islamic character values ??in students at SDN 35, Bengkulu City, is to guide, direct, and provide good role models, as well as consistently instilling moral values ??in students so that these character values ??are firmly embedded in their personalities. With this research, it is hoped that PGMI teachers can effectively internalize Islamic character values ??in students.